Obesity medication lorcaserin activates brainstem GLP-1 neurons to reduce food intake and augments GLP-1 receptor agonist induced appetite suppression - Stefan Wagner; Daniel I. Brierley; Alasdair Leeson-Payne; Wanqing Jiang; Raffaella Chianese; Brian Y.H. Lam; Georgina K.C. Dowsett; Claudia Cristiano; David Lyons; Frank Reimann; Fiona M. Gribble; Pablo B. Martinez de Morentin; et al. (Molecular Metabolism, 2023)
Objective: Overweight and obesity are endemic in developed countries, with a substantial negative impact on human health. Medications developed to treat obesity include agonists for the G-protein coupled receptors glucagon-like peptide-1 (GLP-1R; e.g. liraglutide), serotonin 2C (5-HT2CR; e.g, lorcaserin), and melanocortin4 (MC4R) which reduce body weight primarily by suppressing food intake. However, the mechanisms underlying the therapeutic food intake suppressive effects are still being defined and were investigated here. Methods: We profiled PPG neurons in the nucleus of the solitary tract (PPGNTS) using single nucleus RNA sequencing (Nuc-Seq) and histochemistry. We next examined the requirement of PPGNTS neurons for obesity medication effects on food intake by virally ablating PPGNTS neurons. Finally, we assessed the effects on food intake of the combination of liraglutide and lorcaserin. Results: We found that 5-HT2CRs, but not GLP-1Rs or MC4Rs, were widespread in PPGNTS clusters and that lorcaserin significantly activated PPGNTS neurons. Accordingly, ablation of PPGNTS neurons prevented the reduction of food intake by lorcaserin but not MC4R agonist melanotan-II, demonstrating the functional significance of PPGNTS 5-HT2CR expression. Finally, the combination of lorcaserin with GLP-1R agonists liraglutide or exendin-4 produced greater food intake reduction as compared to either monotherapy. Conclusions: These findings identify a necessary mechanism through which obesity medication lorcaserin produces its therapeutic benefit, namely brainstem PPGNTS neurons. Moreover, these data reveal a strategy to augment the therapeutic profile of the current frontline treatment for obesity, GLP-1R agonists, via coadministration with 5-HT2CR agonists.